Critical Genre Analysis of Thesis Hearing Invitations at the University of Sumatera Utara - Nasution, Atikah Auni; Sinar, Tengku Silvana; Fianda, Afiqah; Jasmine, Shoofy (Universitas Pamulang, 2025)
Thesis hearing invitations are formal academic documents that follow a specific structure and language that reflect institutional norms and adhere to academic communication standards. This study analyzes the rhetorical structure and interpersonal meta-functions in thesis hearing invitations at the University of Sumatera Utara (USU) and how the invitation reflects the professional culture of academic communication. This research uses Critical Genre Analysis (CGA) to explore the structural components and language choices in the invitation, as well as investigate how academic norms are communicated through formal documents. The findings reveal that all thesis hearing invitations consist of four main moves: opening, purpose, content, and closing. However, the number of steps in each move is different. In the invitations, the dominant use of declarative mood emphasizes precise and formal information delivery, typical of academic communication. In addition, the uniformity of the template and the use of formal language according to Indonesian rules emphasize the importance of administrative consistency and professional culture at USU. These practices also reflect a professional culture where clarity, formality, and uniformity are prioritized. Ultimately, this study underscores the value of genre analysis in understanding how genre-specific structures contribute to the effectiveness of academic communication and how they embody institutional values.